The Effect of Different Nitrogen Doses on Yield and Yield Components of Some Sunflower (Helianthus annuus L.) Cultivars Grown as Second Crop - AYDOĞDU, Ahmet; HALİLOĞLU, Hasan (ISPEC Journal of Agricultural Sciences, 2023)
This study investigated the effects of different nitrogen doses on yield and yield components of some sunflower (Helianthus annuus L.) cultivars grown as second crop. The experiment was laid out according to randomized complete block design with split plot arrangements and three replications. Sunflower cultivars (i.e., ‘Bosfora’, ‘P64LE119’ and ‘LG5582’) were kept in the main plots, whereas nitrogen doses (0, 50, 100, 150, 200 kg N ha-1) were randomized in sub plots. Results revealed that the highest plant height and seed yield were recorded for ‘LG5582’ cultivar with 150 and 200 kg N ha-1. The highest seed yield per plant was obtained from ‘LG5582’ cultivar and 200 kg N ha-1. The highest 1000 seed weight was obtained from ‘P64LE119’ cultivar and 200 kg N ha-1. Similarly, the highest hectoliter weight was obtained for 150 and 200 kg N ha-1. Likewise, the highest protein ratio was obtained from ‘Bosfora’ cultivar and the highest oil ratio was recorded for 150 kg N ha-1. The cultivar ‘LG5582’ and 150 kg N ha-1 could be suggested for obtaining higher seed yield and oil ratio.